HUBUNGAN LINGKUNGAN KERJA DENGAN MOTIVASI KERJA PEGAWAI BAGIAN SEKRETARIAT DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SUMATERA BARAT - Sari Andamdewi (Universitas Negeri Padang, 2013)
This research aimed to see work motivation, work environment and relationship between work environment with work motivation in Bagian Sekretariat Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat. The population are all of employees in Bagian Sekretariat Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat amount to 68 people and the samples are 40 people that determined based on Proportional Stratified Random Sampling technique. Instrument used was a questionnaire were formulated based on likert scale and analyzed by Product Moment correlation. The results are significant relationship between work environment with work motivation in Bagian Sekretariat Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat. Key Word : work motivation, work environment